Phenolic Compounds in Red Fruits Produced in Organic Farming at Maturation Stage - Soutinho, Susana (2013)
The agricultural organic farming is different from conventional farming in a way that is aimed at providing a balanced and constructive action in agricultural systems. With the increase in intensive agriculture, undesirable changes were being observed in ecosystems with irreparable damage being caused to the natural equilibrium. This is the reason for the increasing interest in organic farming as an environment friendly agricultural production method. In the present work three red fruits produced in organic farming were analysed, namely raspberry, gooseberry and blueberry. The samples were harvested in a local farm when at plain maturation. The results obtained allowed to conclude that the blueberry contained higher amounts of phenolic compounds, total tannins and total anthocyanins than raspberry and gooseberry. Furthermore, the HPLC analysis allowed to identify monomeric anthocyanins and phenolic acids in the three fruits studied